ANALISA TATA KELOLA IT MENGGUNAKAN DESIGN FACTOR COBIT 2019: STUDI KASUS PT. PETROKIMIA GRESIK - Alhari, Muhammad Ilham; Prisyanti, Affifiana; Ardyanti, Anindia Haliza (Universitas Lancang Kuning, 2024)
This research evaluates the implementation of IT governance at PT Petrokimia Gresik using the COBIT 2019 framework. Information technology (IT) has become a critical component in supporting business operations and strategy, as well as risk management and regulatory compliance. PT Petrokimia Gresik faces challenges in aligning IT with business strategy and ensuring consistent performance. This qualitative case study collected data through interviews and observations. The audit results show that the company focuses on market growth, customer service, innovation, and cost efficiency. COBIT 2019 assisted the company in effectively managing IT applications, systems, and processes, increasing transparency and accountability. Recommendations include improved risk management, optimisation of cloud models, and adoption of Agile and DevOps methods. The implementation of these recommendations is expected to improve operational efficiency, support the achievement of the company's vision and mission as an innovative fertiliser producer, and provide added value in the form of increased productivity, cost savings, and improved service quality. Keywords: COBIT 2019, Information technology, Petrokimia Gresik, Information System, IT Governance